2014
DOI: 10.1155/2014/592709
|View full text |Cite
|
Sign up to set email alerts
|

White Mulberry (Morus alba) Foliage Methanolic Extract Can AlleviateAeromonas hydrophilaInfection in African Catfish (Clarias gariepinus)

Abstract: Two experiments were simultaneously conducted with Morus alba (white mulberry) foliage extract (MFE) as a growth promoter and treatment of Aeromonas hydrophila infection in separate 60 and 30 days trail (Experiments 1 and 2, resp.) in African catfish (Clarias gariepinus). In Experiment 1, four diets, control and control supplemented with 2, 5, or 7 g MFE/kg dry matter (DM) of diet, were used. In Experiment 2, fish were intraperitoneally infected with Aeromonas hydrophila and fed the same diets as experiment 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…The results of the present study indicated that inclusion of U. dioica in the fish diet increased the RBC counts and the values appeared to increase with increasing dietary inclusion levels of U. dioica in healthy fish. The current result is in agreement with observed increase in RBC in: C. carpio fed extract of Eurphobia hirta [57] and Aegle marmelos [58], Clarias gariepinus fed Morus alba extract [59], and juvenile H. huso fed diets supplemented with U. dioica [26]. These results also correspond with those by Nya and Austin [60] who reported the counts of RBC were significantly higher in rainbow trout fed with the garlic-added and ginger-added diets.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study indicated that inclusion of U. dioica in the fish diet increased the RBC counts and the values appeared to increase with increasing dietary inclusion levels of U. dioica in healthy fish. The current result is in agreement with observed increase in RBC in: C. carpio fed extract of Eurphobia hirta [57] and Aegle marmelos [58], Clarias gariepinus fed Morus alba extract [59], and juvenile H. huso fed diets supplemented with U. dioica [26]. These results also correspond with those by Nya and Austin [60] who reported the counts of RBC were significantly higher in rainbow trout fed with the garlic-added and ginger-added diets.…”
Section: Discussionsupporting
confidence: 93%
“…The current result is in agreement with observed increase in RBCs in Cyprinus carpio fed extract of Eurphobia hirta and Aeglemarmellos , Clarias gariepinus fed Morus alba extract (Sheikhlar et al, 2014), and juvenile Huso huso fed diets supplemented with stinging nettle (Urtica diocia) (Binaii et al, 2014). Nya and Austin (2009) also reported higher RBC counts in rainbow trout fed with the garlic-added and ginger-added diets.…”
Section: Hematologicalsupporting
confidence: 91%
“…Against outbreaks of A. hydrophila, several plant extracts as alternative to antibiotics have been tested. These include Origanum heracleoticum in Ictalurus panctatus (Zheng, Tan, Liu, Zhou, Xiang & Wang 2009), Astragalus radix and Ganoderma lucidum in Cyprinus carpio (Yin, Ardo, Thompson, Adams, Jeney & Jeney 2009), Ocimum sanctum in Labeo rohita (Das, Raman, Saha & Singh 2013), Morus alba foliage methanolic extract in Clarias gariepinus (Sheikhlar, Alimon, Daud, Saad, Webster, Meng & Ebrahimi 2014) and Allium sativum in Oncorhynchus mykiss (Nya & Austin 2009). The essential oil (EO) extract have exhibited a wide spectrum of biological activity, thus elicit varying physiological, biochemical and haemato-immunological response in fish.…”
Section: Introductionmentioning
confidence: 99%